Maternal Death Surveillance and Response Systems in driving accountability and influencing change. Issue 3 (December 2016) - Bandali, Sarah; Thomas, Camille; Hukin, Eleanor; Matthews, Zoë; Mathai, Matthews; Ramachandran Dilip, Thandassery; Roos, Nathalie; Lawley, Ruth; Igado, Oko; Hulton, Louise
Abstract: Good progress has been made in reducing maternal deaths from 1990–2015 but accelerated progress is needed to achieve the Sustainable Development Goals (SDGs) in ending preventable maternal deaths through a renewed focus on accountability and actions. This paper looks at how Maternal Death Surveillance and Response (MDSR) systems are strengthening response and accountability for better health outcomes by analyzing key findings from the WHO and UNFPA Global MDSR Implementation Survey across 62 countries. It examines two concrete examples from Nigeria and Ethiopia to demonstrate how findings can influence systematic changes in policy and practice. We found that a majority of countries have policies in place for maternal death notification and review, yet a gap remains when examining the steps beyond this, including reviewing and reporting at an aggregate level, disseminating findings and recommendations, and involving civil society and communities. As more countries move toward MDSR systems, it is important to continue monitoring the opportunities and barriers to full implementation, through quantitative means such as the Global MDSR Implementation Survey to assess country progress, but also through more qualitative approaches, such as case studies, to understand how countries respond to MDSR findings.